2021
DOI: 10.1371/journal.pone.0246279
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis identified differentially expressed proteins with tail/rump fat deposition in Chinese thin- and fat-tailed lambs

Abstract: Tail adipose as one of the important functional tissues can enhance hazardous environments tolerance for sheep. The objective of this study was to gain insight into the underlying development mechanisms of this trait. A quantitative analysis of protein abundance in ovine tail/rump adipose tissue was performed between Chinese local fat- (Kazakh, Hu and Lanzhou) and thin-tailed (Alpine Merino, Tibetan) sheep in the present study by using lable-free approach. Results showed that 3400 proteins were identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…Many studies have attempted to identify the candidate gene associated with tail fat and understand the underlying mechanisms of fat deposition ( Ahbara et al, 2018 ; Amane et al, 2020 ; Baazaoui et al, 2021 ; Bakhtiarizadeh & Alamouti, 2020 ; Dong et al, 2020 ; Han et al, 2021 ; Li et al, 2018a ; Mastrangelo et al, 2019a ; Mastrangelo et al, 2019b ; Moioli, Pilla & Ciani, 2015 ; Moradi et al, 2012 ; Wei et al, 2015 ; Xu et al, 2017 ; Yuan et al, 2017 ; Zhang et al, 2019 ; Zhao et al, 2020 ; Zhi et al, 2018 ; Zhu et al, 2016 ). Previous studies suggested that microRNAs ( Miao et al, 2015a ; Pan et al, 2018 ), lncRNAs ( Bakhtiarizadeh & Salami, 2019 ; He et al, 2020 ) and mRNAs ( Bakhtiarizadeh et al, 2019 ; Kang et al, 2017a ; Miao et al, 2015b ; Wang et al, 2014 ) may regulate tail fat deposition in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify the candidate gene associated with tail fat and understand the underlying mechanisms of fat deposition ( Ahbara et al, 2018 ; Amane et al, 2020 ; Baazaoui et al, 2021 ; Bakhtiarizadeh & Alamouti, 2020 ; Dong et al, 2020 ; Han et al, 2021 ; Li et al, 2018a ; Mastrangelo et al, 2019a ; Mastrangelo et al, 2019b ; Moioli, Pilla & Ciani, 2015 ; Moradi et al, 2012 ; Wei et al, 2015 ; Xu et al, 2017 ; Yuan et al, 2017 ; Zhang et al, 2019 ; Zhao et al, 2020 ; Zhi et al, 2018 ; Zhu et al, 2016 ). Previous studies suggested that microRNAs ( Miao et al, 2015a ; Pan et al, 2018 ), lncRNAs ( Bakhtiarizadeh & Salami, 2019 ; He et al, 2020 ) and mRNAs ( Bakhtiarizadeh et al, 2019 ; Kang et al, 2017a ; Miao et al, 2015b ; Wang et al, 2014 ) may regulate tail fat deposition in sheep.…”
Section: Introductionmentioning
confidence: 99%
“…Both genes belong to the leucine-rich proteoglycan ( SLRP ) family and play important roles in various functions such as collagen fibrillogenesis, cell growth, cell differentiation, and migration [ 48 ]. This was confirmed by a proteomics and gene expression approach [ 49 ], in which thin-tailed sheep had higher ASPN expression levels compared with thick-tailed sheep and was also validated as a protein within the collagen fibril organizing group. In the aforementioned QTL study in pigs [ 47 ], ASPN and OGN genes were identified to be significantly associated with carcass traits at a genome-wide level, specifically loin and neck meat weight, shoulder meat weight, and daily gain (110–210 d).…”
Section: Discussionmentioning
confidence: 79%
“…FASN is a fundamental enzyme in de novo fatty acid biosynthesis [ 40 ]. Studies in sheep have underscored its importance in governing fat deposition and composition, as it affects traits like marbling and adiposity [ 63 ]. ACSL1 performs a crucial role in fatty acid metabolism through the catalysis of acyl-CoA production, a pivotal process in fatty acid activation for various metabolic pathways, such as oxidation and complex lipid synthesis [ 64 ].…”
Section: Resultsmentioning
confidence: 99%